2004
DOI: 10.1099/vir.0.79978-0
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T-cell responses to herpes simplex virus type 2 (HSV-2) glycoprotein G are type specific and differ in symptomatic and asymptomatic HSV-2-infected individuals

Abstract: T-cell recognition of the secreted and membrane-bound portions of the herpes simplex virus type 2 (HSV-2) glycoprotein G (sgG-2 and mgG-2, respectively) was compared in symptomatic and asymptomatic HSV-2-infected individuals and in HSV-2-seronegative controls and the responses with HSV-1 glycoproteins C and E (gC-1 and gE-1) were compared. CD4+ T cells from HSV-2-infected individuals specifically recognized both sgG-2 and mgG-2, whereas HSV-1-infected and HSV-seronegative controls did not respond to these glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 56 publications
(45 reference statements)
3
18
1
Order By: Relevance
“…1). We and others have previously reported that asymptomatic HSV-2 infection is associated with higher T-cell recall IFN-␥ responses, compared with symptomatic HSV-2 in- fection (10,37). However, we could not confirm this observation in the current patient cohort (data not shown).…”
Section: Genetic Variations In Stat4contrasting
confidence: 56%
See 2 more Smart Citations
“…1). We and others have previously reported that asymptomatic HSV-2 infection is associated with higher T-cell recall IFN-␥ responses, compared with symptomatic HSV-2 in- fection (10,37). However, we could not confirm this observation in the current patient cohort (data not shown).…”
Section: Genetic Variations In Stat4contrasting
confidence: 56%
“…However, the treatment of mice with IFN-␥ circumvents the need for CD4 ϩ T cells, which implies that the main function of CD4 ϩ T cells in HSV-2-specific immunity is to produce IFN-␥ (14). The situation is similar in humans, as HSV-2-infected individuals with recurrent disease have impaired virusspecific IFN-␥ responses compared with asymptomatic HSV-2 carriers (10,37).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…This immune escape might be of importance for the pathogenesis of HSV-2, in particular for the establishment of HSV-2 infection in individuals that are already infected with HSV-1. The acquired immune responses to HSV-1 and HSV-2 are, with the exception of the immune response to the gG-2 protein, highly cross-reactive (43)(44)(45)(46)). Yet, HSV-2 manages to infect HSV-1-seropositive individuals as efficiently as it infects individuals with no prior HSV exposure (47), perhaps as a consequence of a gG-2-induced ROS-mediated suppression of specific lymphocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Culture medium was changed, and cells were cultured for the indicated time before next assay. UV-inactivated virus was obtained by exposure of HSV-2 to UV irradiation for 15 min, as described previously (29). To separate virus particles from the cytokines secreted by Vero cells, virus stocks were added to 100-kDa centrifugal filter unit (Millipore) and centrifuged for 30 min at 1000 3 g. Membrane-retained HSV-2 was diluted and used to infect ME-180 cells.…”
Section: Hsv-2 Infectionmentioning
confidence: 99%